Gunung api maar di Semenanjung Muria - Sutikno Bronto; Sri Mulyaningsih (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no1.20074Three maars are well identifi ed in the Muria Peninsula, i.e. Bambang Maar, Gunungrowo Maar, and Gembong Maar. The maars were formed by monogenetic volcanic eruptions due to the interaction between heat source (magma), groundwater and calcareous basement rocks. This interaction is able to produce very high pressure of gas and steam causing phreatic explosions, followed by phreatomagmatic- or even magmatic explosions and ended by a lava extrusion. Satellite image analyses have recognized twelve circular features, comprising Bambang Maar, Gunungrowo Maar, and Gembaong Maar. Phisiographically, these maars are characterized by circular depressions which are surrounded by hills that are gently sloping down away from the crater or having a radier pattern morphology. Outcrops and drilling core in the circular areas that are considered as volcanic maars are lava fl ows, pyroclastic breccias, lapillistones, and tuffs, located far away from the eruption centres of Muria and Genuk Volcanoes. One of the circular features, i.e. Jepara Circular Feature, is also supported by negative anomaly (<30 mgal) showing a circular pattern. In the future, a maar volcano could possibly erupt depending on the tectonic reactivity in the region.